ANALYSIS OF INTERNAL FACTORS THAT AFFECTING THE DECISION OF HEDGING IN COMPANIES MINING SECTORS LISTED ON BURSA EFEK INDONESIA - Mutiara Indah; Isni Andriana; Kemas M. Husni Thamrin (JEMBATAN, 2020)
The aim of this studies were determining and analyzing the internal factors influence the hedging decision of  mining sector company listed on the IDX from 2015-2018 with internal factors, such as financial distress, underinvestment and asset substitution problem. The population of this study consisted of 41 companies. Which was using purposive sampling obtained 12 sampel companies. The analys tecnique used is descriptive statistics. Based on the results of descriptive statistical analys showed there were no companies have been able to meet the average standard of internal factors during the year of this study so many companies have not been able to meet the average standard to do hedging to avoid the risk of internal hedging factors. There was one company has been able to meet the average underinvestment standard, it called the Market to Book Value (MBV) variable during the year of the research, it named namely PT. Bumi Resources Tbk. The next study can be expected to use the company’s hedging disclosure indicators outside of this studies such as external factors there were interest rates and currency exchange and measure the internal factors by adding the variables which can be used to increase the results of the study over all.